The nature of creation : examining the Bible and science - Harris, Mark, 1966-; Cambridge eBooks (Durham : Acumen Publishing, 2013)
It is generally assumed that science and religion are at war. Many now claim that science has made religious belief redundant; others have turned to a literalist interpretation of biblical creation to reject or revise science; others try to resolve Darwin with Genesis. The Nature of Creation addresses this complex debate by engaging with both modern science and biblical scholarship together. Creation is central to Christian theology and the Bible, and has become the chosen battleground for scientists, atheists and creationists alike. The Nature of Creation presents a sustained historical investigation of what the creation texts of the Bible have to say and how this relates to modern scientific ideas of beginnings. The book aims to demonstrate what science and religion can share, and how they differ and ought to differ.
1. Introduction 2. Creation According to Modern Science 3. Creation According to the Bible I: Genesis 4. Creation According to the Bible II: The Creation Motif 5. The Framework of Biblical Creation 6. Creator-Creation: How Can a Relationship Be Described? 7. The Fall 8. Suffering and Evil 9. Scientific Eschatology and New Creation 10. Conclusions.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Creation; Bible and science; Religion and science; Electronic books